2014
DOI: 10.1002/adma.201305849
|View full text |Cite
|
Sign up to set email alerts
|

Janus Nanodisc of Diblock Copolymers

Abstract: Janus nanodiscs of diblock copolymers are prepared by stepwise disassembly of PS-b-P4VP disc-stacked particles. The Janus nanodiscs are uniform in thickness and regular in contour. By preferential growth of functional materials at the positively charged P4VP side, the composition, microstructure, and performance of the Janus nanodiscs are tunable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 37 publications
1
137
0
2
Order By: Relevance
“…38,39 In the current study, 100 μL of chloroform solution containing PS 9.8k -b-P4VP 10k (0.5 wt % in chloroform, the volume fraction of P4VP, f P4VP ≈ 50.5%) was emulsified by ultrasonication in 1.0 mL of deionized water containing PVA (12 mg/mL) as a surfactant, which played dual roles in both stabilizing the emulsion droplets and providing a nearly neutral interface for PS and P4VP blocks. 38,39 Then, the chloroform diffused through the water phase and slowly evaporated, leading to the microphase separation of PS-b-P4VP within the emulsion droplets. After complete removal of chloroform from the emulsion droplets, glassy PS 9.8k -b-P4VP 10k particles with axially stacked lamellar nanostructure were obtained, as shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In the current study, 100 μL of chloroform solution containing PS 9.8k -b-P4VP 10k (0.5 wt % in chloroform, the volume fraction of P4VP, f P4VP ≈ 50.5%) was emulsified by ultrasonication in 1.0 mL of deionized water containing PVA (12 mg/mL) as a surfactant, which played dual roles in both stabilizing the emulsion droplets and providing a nearly neutral interface for PS and P4VP blocks. 38,39 Then, the chloroform diffused through the water phase and slowly evaporated, leading to the microphase separation of PS-b-P4VP within the emulsion droplets. After complete removal of chloroform from the emulsion droplets, glassy PS 9.8k -b-P4VP 10k particles with axially stacked lamellar nanostructure were obtained, as shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that the diblock copolymer is an available candidate if the disk-stacked structure can be disassembled by some appropriate solvents [50]. As shown in Fig.…”
Section: Janus Sheets/disksmentioning
confidence: 99%
“…Some guest species can be encapsulated thereby. Self-assembly approach from block copolymers is proposed to synthesize polymeric Janus nanosheets [37][38][39][40][41]. The block copolymers should possess sufficiently narrow molecular weight distribution in order to form uniform lamellar structure.…”
Section: Introductionmentioning
confidence: 99%